Influence of nutrient density and feed form on growth performance, nutrient digestibility and gastro intestinal tract development in broilers fed wheat-based diets : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatu, New Zealand - Hamungalu, Obright (Massey University, 2019)
This study investigated the influence of nutrient density and feed form, and their interaction on growth performance, nitrogen-corrected apparent metabolisable energy (AMEn) and upper gut components of broilers fed wheat-based diets for 35 d post-hatch. A completely randomised design was used, with a 5 x 2 factorial arrangement of 10 treatments (with 6 replicates, 8 birds per replicate) involving five dietary nutrient density, VL, very low nutrient density (11.71 MJ/kg AMEn, 13.44 g/kg lysine); L, low nutrient density (12.13 MJ/kg AMEn, 13.92 g/kg lysine); M, medium nutrient density (12.55 MJ/kg AMEn, 14.40 g/kg lysine); H, high nutrient density (12.97 MJ/kg AMEn, 14.88 g/kg lysine); VH, very high nutrient density (13.39 MJ/kg AMEn, 15.36 g/kg lysine) and two feed forms, mash vs. pellet. Nutrient density x feed form interaction was significant (P < 0.05) for weight gain and feed intake during finisher and whole grow-out period, while during starter period the interactive effect was significant (P < 0.05) for weight gain. At each nutrient density level, weight gain and feed intake were higher in birds fed pelleted diets than those fed mash diets, but the advantages of pelleting were greater at the lowest nutrient density. During whole trial period feed per unit gain (F/G) significantly (P < 0.001) improved as the nutrient density level increased, but it deteriorated (P < 0.05) due to pelleting. Effect of feed form was significant (P < 0.01) on bird uniformity, with pelleting having 10 % higher uniformity compared to mash diets. Increasing nutrient density had a significant (P < 0.001) effect on AMEn and coefficient of apparent ileal digestibility (CAID) of nitrogen (N), fat, Ca and P. There was a significant (P < 0.05) interaction between nutrient density and feed form for CAID of DM and GE. Pelleting reduced (P < 0.05) the CAID of DM and GE only in M and VH diets and did not have effect (P > 0.05) on these parameters in other nutrient density diets. Feeding pellets lowered (P < 0.05) the CAID of N and starch. Pelleting significantly (P < 0.001) reduced the absolute weight of gizzard compared to mash diets. The gizzard pH of birds fed pellet diet was higher (P < 0.001) than those fed mash diets. In general, the current results show that the pellet-induced benefits on growth performance reduce as the nutrient density levels increase, highlighting the importance of considering nutrient density to maximise the benefits associated with pellet feeding.
Figures 2.1.& 2.2 have been removed for copyright reasons but may be accessed via their source.
Keywords: Broilers (Chickens); Physiology; Feeding and feeds; Feeds; Composition; Wheat as feed; feed form; nutrient density; nutrient digestibility; performance